Report of Joint Study Team Uttar Pradesh (Eastern Districts) Ghazipur Azamgarh Deoria Jaunpur - Planning Commission (Planning Commission, 1964)
With high pressure of population, frequent recurrence of floods and droughts and low productivity in agriculture, the eastern districts of Uttar Pradesh were regarded even in the Second Five Year Plan a low-income area requiring special attention in planned economic and social development. And in the Second and Third Five Year Plans, special allocations were made to accelerate development in these districts. 2. In June 1962. in a debate in the Lok Sabha there was a critical reference to the extremely backward conditions of this region.
Government of India Planning Commission